2016
DOI: 10.1016/j.jacc.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cardiac Magnetic Resonance Imaging in Patients With Suspected Myocarditis

Abstract: In patients with acute symptoms, mapping techniques provide a useful tool for confirming or rejecting the diagnosis of myocarditis and are superior to the LLC. However, only T2 mapping has acceptable diagnostic performance in patients with chronic symptoms. (Magnetic Resonance Imaging in Myocarditis [MyoRacer]; NCT02177630).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
237
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(267 citation statements)
references
References 34 publications
12
237
1
9
Order By: Relevance
“…20 The recognition of acute inflammation by T1 mapping was shown to be superior to edema imaging with T2-weighted sequences [62][63][64] and to LGE. 54,63 This evidence supports a shift in thinking about the current CMR approach to myocarditis. First, native T1 provides excellent positive and negative predictive values Types of sequences and a staining method used, as well as several patients included, are also reported.…”
Section: T1 Mapping In Myocardial Inflammationmentioning
confidence: 57%
See 1 more Smart Citation
“…20 The recognition of acute inflammation by T1 mapping was shown to be superior to edema imaging with T2-weighted sequences [62][63][64] and to LGE. 54,63 This evidence supports a shift in thinking about the current CMR approach to myocarditis. First, native T1 provides excellent positive and negative predictive values Types of sequences and a staining method used, as well as several patients included, are also reported.…”
Section: T1 Mapping In Myocardial Inflammationmentioning
confidence: 57%
“…Endomyocardial biopsy is a proposed, albeit imperfect gold standard for the diagnosis of definitive myocarditis. 52,54 Owing to the variable availability of endomyocardial biopsy expertise, its procedural risks, and a commonly low diagnostic yield, this diagnostic strategy is widely perceived as impractical in most cases of suspected myocarditis. 55,56 In clinical practice, a noninvasive diagnostic pathway, which allows appreciation of disease activity/stage, may also support development of specific therapeutic options, both of which are currently limited.…”
Section: T1 Mapping In Myocardial Inflammationmentioning
confidence: 99%
“…[13][14][15][16] In addition, relevant coronary artery disease had to be ruled out on selective angiography. Patients with contraindication to cardiac catheterization or EMB were excluded.…”
Section: Patient Samplementioning
confidence: 99%
“…16 Recently, CMR has evolved as the gold standard for noninvasive testing. [25][26][27][28] Quantification of LGE can represent a wide variety of tissue processes and has emerged as a diagnostic tool in ischemic heart disease to measure areas of infarction 29 and for risk stratification in ischemic 30,31 and nonischemic heart disease. [32][33][34] Although in clinical practice decreasing cardiac enzymes and inflammatory markers are commonly interpreted as being indicative of resolving myocarditis, no cardiac imaging studies have confirmed this assumption as of today.…”
mentioning
confidence: 99%